35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-3744
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on Rotor-to-Rotor Interactions of Small UAV Propellers

Abstract: In the present study, an experimental investigation was performed to study the effects of rotor-to-rotor interactions on the aerodynamic and aeroacoustic performances of small UAVs. It was found that, while the thrust coefficients of rotor were independent of the separation distance, the thrust fluctuations were found to increase dramatically as the separation distance decreased. An enhancement of ~ 250% was confirmed for the twin-rotor case (i.e., L= 0.05D) in comparison with that of the single rotor case, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 10 publications
(11 reference statements)
6
72
1
Order By: Relevance
“…6 (left), where features of the topology can be clearly identified: a well-defined structure in the near field (z < 0.5D), an onset of leapfrogging at z ≈ 0.5D, and a transition into turbulent breakdown at z ≈ 1.0D. The simulation converges to a mean C T of 0.1013 and a steady fluctuation (standard deviation) of 0.001, meanwhile Zhou et al 18 and Ning 19 report an experimental mean C T of 0.1007 and a fluctuation of 0.008. This results in an error of only 0.5% between the simulation and experimental mean C T , meanwhile the fluctuation is largely underpredicted.…”
Section: Iiia Hover Casementioning
confidence: 85%
See 4 more Smart Citations
“…6 (left), where features of the topology can be clearly identified: a well-defined structure in the near field (z < 0.5D), an onset of leapfrogging at z ≈ 0.5D, and a transition into turbulent breakdown at z ≈ 1.0D. The simulation converges to a mean C T of 0.1013 and a steady fluctuation (standard deviation) of 0.001, meanwhile Zhou et al 18 and Ning 19 report an experimental mean C T of 0.1007 and a fluctuation of 0.008. This results in an error of only 0.5% between the simulation and experimental mean C T , meanwhile the fluctuation is largely underpredicted.…”
Section: Iiia Hover Casementioning
confidence: 85%
“…In contrast, distributed propulsion eVTOL aircraft are typically wing-borne during cruise, and the axes of rotation of the rotors are roughly aligned with the direction of flight, with the velocity of the aircraft adding directly to the axial inflow and advance ratio of the rotors. Even though previous studies have shown that multirotor interactions could drop the thrust performance by only a small amount [15][16][17]20 (∼4% relative to the isolated rotor), they also show that noise could be increased by as much as 3 dB, 18,19 corresponding to an acoustic signature two times more intense, which is a critical factor to consider in the design of urban mobility aircraft. Experimental results indicate that this increase in noise is directly related to unsteady loading during aerodynamic interactions.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations